اﻟﻌزﻟﺔ اﻻﺟﺗﻣﺎﻋﯾﺔ ﻟدى اطﻔﺎل اﻟرﯾﺎض (Journal of the College of Education for Women, 2019)
The human being is considered to be by nature a social creature who tends to live among a certain group feeling safety ,stability and tranquility and satisfies his needs for belonging and through it is personality outs stands ,and be absorbs from it the social and ethical standards and the impotent psychological trends and holds on to its members and makes with it mutual relations and when he cannot make this holding on of safety then his relations with the members of the group are negatively affected so he withdraws away from them in a loneliness and solitude . One of the reasons of the development of the social solitude in the child is the family and that is through the process of the social upbringing in the Childs bringing up at which when the family uses the wrong and unsound educational ways with the child it will be reflected on his personality and behavior in the negative direction. The importance of the research is because it is concerned in an important category which is kindergarten children , and it also decals with the human personality appearances and it is the social solitude and which has a great influence on the psychological health . and the current research aims at : 1) Knowing the individual differences in the level of the social solitude in kindergarten children according to: -sex (male, female) -stage (kindergarten, preliminary) 2) Revealing the level of thesocial solitude in kindergarten children